Lessons in typography must-know typographic principles presented through lessons, exercises, and examples - Krause, Jim 1962- (Creative core, 2016)
"Get hands on with type in this lesson-based addition to Jim Krause's popular new Creative Core series on design fundamentals. In Lessons in Typography, you'll learn the basics of identifying, choosing, and using typefaces and immediately put that knowledge to work through a collection of exercises designed to deepen and expand your typographic skills. After a crash course in type terminology, you're encouraged to walk the talk with lessons and exercises on creating type-based logos, crafting personal emblems, choosing and using the right fonts for layouts, designing your own fonts, fine-tuning text like a professional, hand lettering, and more. Krause uses practical advice, humor, and page after page of visual examples to give you a complete education in designing with type that you can read in a matter of hours and continue to learn from over the course of your career."--Back cover.